Hydrology and floodplain analysis Philip B. Bedient, Wayne C. Huber, Baxter E. Vieux; internation edition contributions by Muralidhar Mallidu - Bedient, Philip B. 1948-; Huber, Wayne Charles; Vieux, Baxter E.; Mallidu, Muralidhar (Pearson, 2013)
This text offers a clear and up-to-date presentation of fundamental concepts and design methods required to understand hydrology and floodplain analysis. It addresses the computational emphasis of modern hydrology and provides a balanced approach to important applications in watershed analysis, floodplain computation, flood control, urban hydrology, stormwater design, and computer modeling.